Can You Trust a Box Diet? - Orkusz, Agnieszka; Dobrzyńska, Daniela (Czy możesz zaufać diecie pudełkowej?, 2022)
In recent years the pace of human life has increased significantly. Sometimes, overworked people do not have time to prepare five meals a day by themselves, and use the services of catering companies offering ready-made meals that are delivered directly to the client’s place of work or residence in the form of a box.. This study aimed to evaluate the diet of individual customers based on the standard diet developed by one of the companies (the company was randomly chosen) engaged in dietary catering based in Lower Silesia. This evaluation was carried out based on menus prepared for ten days. For this purpose, the Diet 6D programme, developed by the Institute of Food and Nutrition in Warsaw, was used. The amounts of basic nutrients in the standard dietary menus adopted by the catering company did not comply with the recommendations for a rational diet. The advantage of the served meals was that the customers were offered a daily variety of meals rich in vegetables and fruit.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2022, Nr 38, s. 124-133